Hepatic glucose uptake and disposition during short-term high-fat vs. high-fructose feeding - Coate, Katie C. (American Physiological Society, 2014)
In dogs consuming a high-fat and -fructose diet (52 and 17% of total energy, respectively) for 4 wk, hepatic glucose uptake (HGU) in response to hyperinsulinemia, hyperglycemia, and portal glucose delivery is markedly blunted with reduction in glucokinase (GK) protein and glycogen synthase (GS) activity. The present study compared the impact of selective increases in dietary fat and fructose on liver glucose metabolism. Dogs consumed weight-maintaining chow (CTR) or hypercaloric high-fat (HFA) or high-fructose (HFR) diets diet for 4 wk before undergoing clamp studies with infusion of somatostatin and intraportal insulin (3–4 times basal) and glucagon (basal). The hepatic glucose load (HGL) was doubled during the clamp using peripheral vein (Pe) glucose infusion in the first 90 min (P1) and portal vein (4 mg·kg(−1)·min(−1)) plus Pe glucose infusion during the final 90 min (P2). During P2, HGU was 2.8 ± 0.2, 1.0 ± 0.2, and 0.8 ± 0.2 mg·kg(−1)·min(−1) in CTR, HFA, and HFR, respectively (P < 0.05 for HFA and HFR vs. CTR). Compared with CTR, hepatic GK protein and catalytic activity were reduced (P < 0.05) 35 and 56%, respectively, in HFA, and 53 and 74%, respectively, in HFR. Liver glycogen concentrations were 20 and 38% lower in HFA and HFR than CTR (P < 0.05). Hepatic Akt phosphorylation was decreased (P < 0.05) in HFA (21%) but not HFR. Thus, HFR impaired hepatic GK and glycogen more than HFA, whereas HFA reduced insulin signaling more than HFR. HFA and HFR effects were not additive, suggesting that they act via the same mechanism or their effects converge at a saturable step.